CONCEPTUAL METAPHORS OF LOVE IN LYRICS BY BEE GEES / Trần Thị Thúy; NHDKH Đặng Nguyên Giang, Ph.D - Trần, Thị Thúy
The title of my thesis is Conceptual metaphors of love in lyrics by Bee Gees. The study is carried out with a view to pointing out conceptual metaphors of love in lyrics by Bee Gees. In the thesis, structural and ontological metaphors are specially analyzed to reflect the opinions of the composers about love between lovers. The study is employed through the documentary analysis and descriptive study with the help of qualitative and quantitative approach. All the lyrics of the songs by Bee Gees describe the target concepts of love with nine typical patterns of structural metaphors such as LOVE IS LIGHT, LOVE IS CLOSENESS, LOVE IS A JOURNEY, LOVE IS SADNESS, LOVE IS POWER, LOVE IS PAIN, LOVE IS BELIEFE, LOVE IS MUSIC and LOVE IS A DREAM and seven typical patterns of ontological metaphors such as LOVE IS A PRISON, LOVE IS A PARADISE, LOVE IS A PLANT, LOVE IS AN ANIMAL, LOVE IS A SOURCE OF WARMTH, LOVE IS AN OBJECT and LOVE IS A FLAME. It is really obvious that each concept represents our thoughts, experiences about love and open to our everyday life. As a whole, this study has been conducted on conceptual metaphors of love in Bee Gees’ love songs in a hope that learners will get some benefits from this study to have keenness for learning English in general and metaphors of love better in particular.